Efektivitas Pelayanan Pengaduan Masyarakat Melalui Doorstop di Kecamatan Kebayoran Baru Kota Administrasi Jakarta Selatan - Kasmawati Kasmawati (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
The purpose of this study is to analyze the effectiveness of public complaints services through Doorstops, to find out the supporting and inhibiting factors for the point of public protests services through Doorstops, and efforts to overcome barriers to the effectiveness of Public Complaints Services through Doorstops in Kebayoran Baru District, South Jakarta Administration, DKI Jakarta Province. The method used in this study is a qualitative method with a descriptive approach. The data needed in this study include primary data and secondary data. This research used data collection techniques through interviews, documentation and observation. Informants were determined using purposive sampling and incidental sampling techniques. According to Gibson, Ivancevich, Donnelly (1995), the theory used is the basis for developing a framework of thinking and research instruments. It appears that there are several problems, including the number of complaints received is still very small and even decreased from 2017-2019, the amount of budget used is not proportional to the number of services provided, the service process is still prolonged, there are still some repeated complaints, human resources still lacking, the facilities and infrastructure used are still minimal, and socialization has not been maximized so that it has an impact on decreasing public complaint services. Suggestions to increase productivity and quality of general complaint services, re-evaluate the budget used, increase Human Resources, fulfil infrastructure, and socialize, as well as optimize online-based public complaint services.